Digital divide among firms in ASEAN before, during, and after the COVID-19 pandemic - Keita Oikawa; Fusanori Iwasaki; Yasushi Ueki; Shujiro Urata (International Telecommunications Society (ITS), 2024)
The study conducted a comprehensive examination of the digital divide in the ASEAN region through a large-scale questionnaire survey targeting regional MSMEs. Two types of surveys, web and phone, were employed to capture a diverse range of responses, considering company size, industry, and geographical location. Findings reveal that before COVID, basic digital devices and e-payment systems were widely adopted, even by entry-level firms, while other digital tools saw limited adoption, widening the digital divide. Post-COVID, digitally developed firms accelerated their adoption of digital tools, especially web conferencing and e-commerce, while entry-level firms showed little progress. The study identifies a five-stage progression in digital tool adoption, highlighting the need for tailored support at each stage. Firm attributes significantly influenced adoption: economic development levels positively affected smaller firms, firm size consistently impacted adoption, and rural firms were not disadvantaged. FDI and ownership structure also played crucial roles, with FDI firms adopting a broader range of tools but lagging in advanced tools. Participation in global value chains positively influenced adoption, especially at higher stages. Public and private support benefited digitally developed firms but was less effective for entry-level firms, indicating a need for targeted support mechanisms. The study underscores the connection between digital tool adoption and improved business performance post-COVID, with digitally developed firms experiencing positive growth and entry-level firms showing increased robustness. The findings suggest that policymakers should provide targeted assistance, enhance support access, and address stage-specific challenges to ensure all firms benefit from digital transformation initiatives.
Keywords: 330